Reformulation of Tax Consultant Ethics: Strategic Partnertners in Indonesia’s Self-Assessment System - Nofrianti Madin; Santi Novita; Heru Tjaraka (Amkop Management Accounting Review (AMAR), 2026)
This study aims to review the concept of professional ethics for tax consultants to align with the integrity principles needed in implementing the self-assessment system in Indonesia. This study uses an exploratory qualitative approach, with data collection methods including a literature review and in-depth interviews with practitioners and academics. Research shows that tax consultants are prone to ethical violations due to weak moral values, pressure from clients, and the lack of an effective supervision system. This situation is made worse by the fact that the code of ethics is still mostly normative and hasn't kept up with developments in tax practice. A reformulation of ethics is needed that focuses on strengthening values of integrity, accountability, and applying good governance principles. The implications of this research point to the importance of enhancing ethical capacity through ongoing training and increasing the role of professional associations in ethical oversight. The novelty of this study lies in proposing a contextual transformative ethical framework and redefining the role of tax consultants as strategic partners in supporting the national tax system.